Herpes simplex virus type 1 persistence and latency in cultured rabbit corneal epithelial cells, keratocytes, and endothelial cells. Issue 9 (September 1986) - Cook, S D; Brown, S M
Abstract : Cell cultures of rabbit corneal epithelium, keratocytes, and endothelium were used to determine the lytic cycle of herpes simplex virus type 1. Viral growth was fastest in epithelial cells. A novel HSV-1 in-vitro latency system was established in the three distinct cell types. Cell cultures were inoculated at low multiplicities of infection with HSV-1. Temperature manipulation alone was used to induce and reactivate latent HSV-1 infections. The presence of cellular stress proteins was demonstrated at supraoptimal temperatures. All cell types were capable of maintaining latent viral infections under these conditions. Viral persistence was present in 20% of epithelial cell cultures at supraoptimal temperatures, but not in keratocyte cultures or endothelial cell cultures.